Estudo e adequação dos principais elementos do modelo canadense de construção em wood frame para o Brasil - Zaparte, Taiara Aparecida (2014)
This work introduce a study of the main elements of Canadian wood frame construction system, to further assess which of these are interesting to use in Brazil and which require adaptation. The research is characterized as a literature review focused on the manual Canadian wood frame house construction and support in international books, seeking to serve as a reference for designers and performers, as yet there is little study in this area in Brazil, and therefore the difficulty of find information on Brazilian literature. This work also addresses the issue of sustainable wood frame system, since the construction industry is one of the sectors of the economy that generates more waste and therefore has great impact on the environment and quality of life. Thus, there is a need to further study and thought sustainable technologies. Finally, the study showed that the wood frame system may be advantageous in relation to methods commonly used in Brazil, requiring few adjustments especially regarding the closure panels and the choice of the foundation structure.